2003
DOI: 10.2139/ssrn.648164
|View full text |Cite
|
Sign up to set email alerts
|

Capital and Risk: New Evidence on Implications of Large Operational Losses

Abstract: Operational risk is currently receiving significant media attention, as financial scandals have appeared regularly and multiple events have exceeded one billion dollars in total impact. Regulators have also been devoting attention to this risk, and are finalizing proposals that would require banks to hold capital for potential operational losses. This paper uses newly available loss data to model operational risk at internationally active banks. Our results suggest that the amount of capital held for operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 14 publications
6
37
0
Order By: Relevance
“…Chernobai et al (2009) …nd that there is a strong link between individual operational events and …rm-speci…c covariates, whereas the macroeconomic environment has less e¤ect. Although this …nding suggests that operational risk is idiosyncratic, de Fontnouvelle et al (2006) fail to reject the hypothesis that the loss severity distribution across similar institutions is the same; a reason which underpins the usefulness of external data. The main bene…t of participating in a data consortium comes from the fact that it contributes to a better operational risk management, helping to avoid the massive value destruction that operational shocks may cause.…”
Section: Related Literaturementioning
confidence: 75%
“…Chernobai et al (2009) …nd that there is a strong link between individual operational events and …rm-speci…c covariates, whereas the macroeconomic environment has less e¤ect. Although this …nding suggests that operational risk is idiosyncratic, de Fontnouvelle et al (2006) fail to reject the hypothesis that the loss severity distribution across similar institutions is the same; a reason which underpins the usefulness of external data. The main bene…t of participating in a data consortium comes from the fact that it contributes to a better operational risk management, helping to avoid the massive value destruction that operational shocks may cause.…”
Section: Related Literaturementioning
confidence: 75%
“…As shown in Moscadelli (2004), de Fontnouvelle (2005, de Fontnouvelle et al (2003), de Fontnouvelle et al (2005), and further discussed in Fiordelisi et al (2014), Neslehová et al (2006) and Peters and Shevchenko (2015), a peculiar characteristic of operational risk is that the distribution of losses is extremely heavy tailed, showing a clear Paretian behaviour for the upper tail, when we consider losses as positive amounts. Following the standard division of banks' activities into business lines, as required by the so-called standardized and advanced measurement approaches (BCBS 2011b, Moscadelli 2004 has even shown that for corporate finance, trading and sales and payment and settlement, the loss distribution has a deal with its extremely heavy-tailed behaviour, e.g.…”
Section: Introductionmentioning
confidence: 76%
“…In particular in the field of financial literature, operational risk measurement has received significant attention (Embrechts et al 2003;De Fontnouvelle et al 2006) and is closely followed in practice (Frachot et al 2007;. The main approach to quantifying operational risk is related to the calculation of VaR and Conditional VaR (CVaR) which is also termed Expected Shortfall (ES) by banks and insurance companies (Rockafellar and Uryasev 2002).…”
Section: Operational Risk Measurement In Financial Services and Manufmentioning
confidence: 99%